An abnormal country - Steven Rosefielde (Bank of Finland, Institute for Economies in Transition (BOFIT), 2004)
Andrei Shleifer and Daniel Treisman recently rendered a summary verdict on the post-Soviet Russian transition experience finding that the Federation had become a normal country with the west's assistance, and predicting that it would liberalize and develop further like other successful nations of its type.This essay demonstrates that they are mistaken.It shows factually, and on the norms elaborated by Pareto, Arrow and Bergson that Russia is an abnormal political economy unlikely to democratize, westernize or embrace free enterprise any time soon.
URN:NBN:fi:bof-201408071894
Keywords: P30; P40; P51; P52; 330; Russia; transition; welfare